The Linguistic Demands of the Common Core State Standards for Reading and Writing Informational Text in the Primary Grades - Roberts, Kathryn L. (Seminars in Speech and Language, 2012)
Forty-five states and four U.S. territories have committed to implementing the new Common Core State Standards, with the goal of graduating students from our K–12 programs who are ready for college and careers. For many, the new standards represent a shift in genre focus, giving much more specific attention to informational genres. Beginning in the primary grades, the standards set high expectations for students’ interaction with informational text, many of which are significantly more linguistically demanding than the standards that they replace. These increased demands are likely to pose difficulties not only for students currently receiving language support, but also for students without identified delays or disabilities. This article describes several of the kindergarten through fifth-grade standards related to informational text, highlighting the linguistic demands that each poses. In addition, instructional strategies are provided that teachers and speech-language pathologists can use to support the understanding and formulation of informational text for listening, reading, speaking, and writing.
Keywords: common core state standards; informational text; literacy; linguistic demands; speech-language pathologists